The effect of 6 weeks of high-intensity interval training (HIIT) with using Nano-curcumin supplement on total antioxidant capacity and Malondialdehyde level in overweight girls - Somaye Fakhri; Saeed Shakeryan; Fatemeh Fakhri; Aliakbar Alizadeh (مجله دانشگاه علوم پزشکی بیرجند, 2019)
Background and Aim: Despite the positive effects of high-intensity interval training (HIIT), these training cause oxidative stress due to high intensity. Therefore, the purpose of this study was to investigate the effect of 6 weeks of HIIT training by using Nano-Curcumin supplement on total antioxidant capacity and Malondialdehyde level in overweight girls. Materials and Methods: The present study was a quasi-experimental study with a pretest-posttest design. Accordingly 48 overweight girl students with average age (21.78 ±0.94 years) and BMI (28.12±2.1 Kg/m2) were entered randomly and equal divided into four groups: training group (n=12), training-supplement (n=12), supplement (n=12) and control group (n=12). Supplemental groups consumed an 80 mg capsule of Nano-Curcumin daily. Training groups, three sessions per week for 6 weeks performed HIIT exercises with 85 to 95% of maximum heart rate. Before and after training and consumption the supplementation, Blood samples were obtained to measure Malondialdehyde indices and total antioxidant capacity. Results: In the present study, there was a significant decrease in Malondialdehyde levels (P = 0.009) and a significant increase in total antioxidant capacity (P=0.01) in the training-supplement group while levels of Malondialdehyde increased significantly (P = 0.004) in the training group. Conclusion:  It seems, intense HIIT training causes oxidative stress in overweight people, concomitant use of the supplement may possibly improve the total antioxidant capacity in overweight people.